PURCHASING BEHAVIOR OF Y GENERATION TOWARDS DOMESTIC AND FOREIGN PRODUCTS BASED ON ETNOCENTRIC TENDENCIES: AFYONKARAHİSAR SAMPLE (Third Sector Social Economic Review, 2021)
With the rapid spread of globalization and the development of the international market, a product at one end of the world can easily be delivered to a consumer at the other end of the world. At this time, as the entry and exit of products between countries is quite facilitated, firms may encounter some problems in new markets. One of these problems is consumer ethnocentrism. The concept of consumer ethnocentrism discusses whether the use of foreign products is morally appropriate and can be expressed as the tendency to prefer domestic products instead of foreign products. The high ethnocentric tendency in the markets to which foreign firms are to penetrate leads to the prejudice against the products of those firms. Foreign companies aiming to enter the market of other countries will gain competitive advantage by learning the ethnocentric tendency levels of the consumers in that market and developing appropriate marketing strategies. In the study, the relationship between demographic characteristics and ethnocentric tendencies of Y generation members is examined. The levels of ethnocentric tendency of these generation members against domestic and foreign products have been determined. Attitudes and behaviours towards products categorized as shop-store and expensive- luxury have been examined and the relationship between them and ethnocentrism has been examined. The data obtained  in the survey were collected by means of the questionnaire from members of 500 Y generation living in Afyonkarahisar province through ""convenience sampling method"". The methods such as frequency, mean, percentage were used when analyzing SPSS program which is the means of making statistical analyzes in collected data. One-Way ANOVA test was used for the analysis of three or more groups with normal distribution, and Pearson Chi-Square test was used for the analysis of qualitative data. As a result, it is found that Y generation members have moderate ethnocentric tendencies.
Keywords: Ethnocentrism; consumer ethnocentrism; Y generation; domestic product; foreign product